Air Transport and Energy Efficiency - World Bank (Washington, DC, 2014)
The air transport sector is enjoying an optimistic growth rate while at the same time eliciting growing concern, due to its environmental impact and its vulnerability with respect to energy security. These issues have put the sector at the forefront of the tide in achieving energy efficiency. Efforts have been made on every front to improve efficiency through better technology, optimized operation, as well as energy-saving infrastructure. This report includes five chapters. Chapter 1 will introduce the air transport energy consumption outlook though the analysis of the growth of air services as well as consumption of fossil fuel-based energy. Chapter two will discuss air transport's impact on the environment and the response and actions from the air transport sector. Chapter three will detail potential energy efficiency gains in aircraft design, air service operation, as well as infrastructure design. The role of the government and private sector in fostering and supporting those energy efficiency gains will also be discussed. Chapter four will enumerate policy options for countries with respect to air transport energy efficiency, focusing on fiscal measures. Finally, chapter five presents an analysis of support and financing measures that can be taken by the World Bank and its member countries. This report compiles a maximum of information on the issues culled from existing research as well as from open sources provided by partner organizations and industry. It aims to guide the air transport industry, policy makers, and development institutions on where to focus their investments or support in developing and emerging markets in order to address the energy and climate change challenges ahead.